Fatty Acid Composition and Physiochemical Properties in Germinated Black Rice - Siska Indriarsih; Mary Astuti; Sri Kanoni (Indonesian Association of Food Technologists, 2017)
The objective of the research was to determine the effect of the germination of black rice. Black rice was soaked for 12 h and further germinated for 12, 24, 36, and 48 h. Non-germinated black rice was used as a control. Black rice was germinated for 19-20 h. Fat, and moisture content, total sugar, cooking quality, sensory analysis, and fatty acid composition of germinated black rice were further evaluated. Results show that fat content decreased during germination, but moisture content and total sugar increased. Physiochemical properties, such as length expansion ratio, volumetric expansion, water absorption, gel consistency, and alkali values were in the ranges of 0.77-0.91 mm, 2.42-3.38, 1.64-2.04, 66-82.5 mm, and 2-3.5, respectively. From sensory analysis, most of panelists were favorable for the germinated black rice at 24 h germination. SFA and MUFA tended to decrease during germination but PUFA tended to increase. Thus the germination is effective to improve nutritional values of black rice